Electrochemical Investigation of Anthraquinone-Based Chemodosimeter for Cu2+ Metal Ion - Yeo Woon Yoon; Jong Seung Kim; Tae Hyun Kim (Journal of Chemistry)
The electrochemical properties of an anthraquinone-containing Cu2+-promoted desulfurization chemodosimeter (AQCD) in the presence of various metal ions were investigated by voltammetry. AQCD showed voltammetric changes toward divalent metal ions (M2+), which are similar to those of anthraquinone (AQ) and 1-aminoanthraquinone (AQNH2) with the metal ions except Cu2+. This can be explained on the electrostatic interaction (AQCD-M2+) and chemodosimetric reaction (AQCD-Cu2+).